Analisis Kebutuhan Raw Material dan Penggunaan Mesin Guna Memaksimalkan Proses Produksi Pada UD Gajah Delta - Dian Novita Rahayu; Elisabeth Lidya Yulianti; Praditya Dimas Santosa; Rizky Andrian Firnanda; Hery Murnawan (Institut Teknologi Adhi Tama Surabaya, 2023)
UD Gajah Delta is a familly business managed by a husband and wife in the city of Sidoarjo, East Java. This trading business was started in the 2000s and still survives today. One of UD Gajah Delta's strategies to survive today is to maintain quality and pay attention to every detail of the voice of the customer. In fulfilling the demand for pans, meatball boilers, rice boilers, and soup bowls, UD has 3 factories and dozens of employees who help with the production process. Besides that, to help the success of the production process, there are various types of machines such as cutting machines, press machines, press roll machines, and punch machines. In order to maximize the production process at UD Gajah Delta, it is necessary to calculate the need for raw materials and the number of machines used to assist the production process. Calculating the need for raw materials and machines used can use the method of operation process chart (OPC) and multi product process chart (MPPC). So that it will know the amount of raw material requirements and the right machine in the production process.Keywords: Raw material, MPPC, OPC, Machine